Mineralogy and deformation structures in components of clastic sediments from the Morasko meteorite lake - Duczmal-Czernikiewicz, Agata Duczmal; Choiński, Janusz; Ptak, Mariusz; Muszyński, Andrzej (Bulletin of Geography. Physical Geography Series, 2018)
The paper presents mineralogical analysis of sediments of the biggest lake formed on the Morasko Meteorite Reserve (Poland) in terms of presence of matter of their origin. The lake are filled by phytogenic sediments at the top, while at their bottom occur Neogene clays. The main components are: clay minerals in fine fraction and quartz and feldspars in coarse sandy fractions. The presence of disturbed ferrous zones suggests the existence of a dynamic factor that caused deformations in the sediments. Cavities, crevices, cracks, and traces of parching or fragmentation of mineral material can be interpreted as deformations related to the impact of meteorite fragments in non-consolidated soft sediments in the Morasko meteorite nature reserve. Meteorite fragments that left numerous deformed structures most probably constituted meteorite debris that originated from the fragmentation of the meteorite before its impact.